ANALYSIS OF TRAINING PROGRAMS TO IMPROVE THE PERFORMANCE OF GUNUNGSITOLI CITY BPBD EMPLOYEES - Roshati Dakhi; Meiman Hidayat Waruwu; Tiarni Duha; Sukaaro Waruwu (Jurnal Ilmiah METADATA, 2026)
This study aims to analyze the effectiveness of training programs implemented at the Gunungsitoli City Regional Disaster Management Agency (BPBD) and identify training needs to improve employee performance. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with six key informants, namely the Head of the Service, the Secretary of the Service, the Head of the General and Personnel Sub-Division, the Head of the Prevention and Preparedness Division, the Head of the Emergency and Logistics Division, and the Head of the Rehabilitation and Reconstruction Division. Data analysis was carried out using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing, and supplemented with thematic analysis to identify patterns and main themes from the interview data. The research results show that the training program implemented by the Gunungsitoli City Regional Disaster Management Agency (BPBD) has had a positive impact on improving technical skills, response speed, mental preparedness, and employee confidence. Existing training is largely relevant to dominant disasters such as floods and landslides. However, the effectiveness of the training remains limited due to its short duration, limited facilities, disparities in training access among employees, and a lack of systematic evaluation mechanisms. Identification of training needs revealed the need for multi-hazard training, improved decision-making and inter-agency coordination skills, mental preparedness, utilization of the latest technology, and more realistic field simulations. The conclusion of this study confirms that training at the Gunungsitoli City Regional Disaster Management Agency (BPBD) has contributed to improving employee performance, but still requires strengthening aspects of needs-based planning, extending training duration, improving evaluation, and providing support for facilities and the organizational environment. The researchers recommend the need for a holistic capacity-building approach to strengthen the capacity of individuals, organizations, and the supporting environment in disaster management.